Upstream and Downstream Malay Dialect in the East Coast of Peninsular Malaysia: (Dialek Melayu Hulu dan Hilir di Timur Semenanjung Malaysia) (Jurnal Bahasa, 2018)
This paper intends to examine the Malay dialect spoken in the upstream and downstream areas of three main river basins in the eastern part of the Peninsula: the Pahang river basin, Kelantan river basin and Terengganu river basin. Based on the phonological and phonetic comparisons (both synchronic and diachronic), this paper tries to answer one important issue, that is to show similarities and differences pertinent to the dialects spoken in the aforementioned areas. In other words, the study aims to explain the defining linguistic features of the dialects. Interestingly, the analysis found that the spoken dialects in the upstream areas have different linguistic features compared to the dialects in the downstream area. These findings prove that a sharp boundary (isogloss) can be established to distinguish the dialects in the two areas. There are at least two implications from this study. Firstly, that the topographic system is still a viable instrument in Malay dialect research, especially in mapping dialectal borders. This leads to the second implication, that the classification of Malay dialects should also be based on the topographic system.Keywords: upstream dialects, downstream dialects, East Peninsular Malaysia, topographic system, river basins